Windows upon planning history
1 online resource (296 pages)
Keywords: Windows Upon Planning History delves into a wide range of perspectives on urbanism from Europe, Australia and the USA to investigate the effects of changing perceptions and different ways of seeing cities and urban regions. Fischer, Altrock and a team of 13 distinguished authors examine how and why the ideologies and the processes of city making changed in modern and post-modern times.